FAKTOR-FAKTOR YANG MEMPENGARUHI FIRM VALUE DENGAN MODERASI KEPEMILIKAN MANAJERIAL - Yonatan, Aurelius Matthew; Rasyid, Ardiansyah (Jurnal Paradigma Akuntansi, 2024)
The purpose of this research is to analyze and obtain empirical evidence regarding the effect of capital structure, profitability, and firm size on firm value with a moderating variable, namely managerial ownership. This study uses 114 data samples from manufacturing companies that have been listed on the Indonesia Stock Exchange during the 2018-2020 period. In this study also used Eviews 12 to perform research data processing. The results obtained from the study are that capital structure has a positive and insignificant effect on firm value. Profitability has a positive and significant effect on firm value. Firm size has a negative and insignificant effect on firm value. In addition, managerial ownership is not able to moderate the relationship between capital structure, profitability, and firm size with firm value.